2006
DOI: 10.3366/e1471576707000058
|View full text |Cite
|
Sign up to set email alerts
|

Excavation of a Possible Neolithic Structure, Lithic Finds and Later Ditch Features at Kingarth Quarry, Isle of Bute

Abstract: Topsoil stripping in advance of an extension to sand and gravel quarrying operations at Kingarth, Isle of Bute, revealed a series of ditches, the remains of a small oval structure and discrete concentrations of worked stone artefacts. The site is situated on a raised beach deposit on the east-facing Kilchattan Bay. The ditches formed a discrete grouping on the higher, gravel deposits in the westernmost part of the site whilst the oval structure, defined by a shallow slot trench and enclosing an area measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The majority seem to be rectangular in plan, with light timber frames, such as Kinbeachie Farm, Highland (Barclay et al 2001) and Biggar Common, South Lanarkshire (Johnston 1997). A number of undated rectangular structures have also been tentatively interpreted as Neolithic houses, such as Kingarth, Bute (Mudie & Richardson 2006) and Ratho Quarry, Edinburgh (Smith 1995). In themselves, this small group of negative features does not amount to a tradition, but suggests that there were light timber-framed buildings in Scotland in the Neolithic.…”
Section: Camps and Timber-built Buildingsmentioning
confidence: 99%
“…The majority seem to be rectangular in plan, with light timber frames, such as Kinbeachie Farm, Highland (Barclay et al 2001) and Biggar Common, South Lanarkshire (Johnston 1997). A number of undated rectangular structures have also been tentatively interpreted as Neolithic houses, such as Kingarth, Bute (Mudie & Richardson 2006) and Ratho Quarry, Edinburgh (Smith 1995). In themselves, this small group of negative features does not amount to a tradition, but suggests that there were light timber-framed buildings in Scotland in the Neolithic.…”
Section: Camps and Timber-built Buildingsmentioning
confidence: 99%
“…Scottish non-Arran assemblages are mostly in aphyric pitchstone, although recent research has shown that, occasionally, porphyritic pitchstone may be present in small numbers. Only the recently discovered assemblage from Blackpark Plantation East on Bute (Ballin et al forthcoming), and assemblages from adjacent Bute sites (for example, Dunagoil, The Plan and Kingarth Quarry; Mann 1918, 147;Finlay 2003;Mudie & Richardson 2006), are dominated by porphyritic material.…”
Section: The Archaeological Evidencementioning
confidence: 99%